2013
DOI: 10.1152/jn.01074.2012
|View full text |Cite
|
Sign up to set email alerts
|

pH modulation of glial glutamate transporters regulates synaptic transmission in the nucleus of the solitary tract

Abstract: The nucleus of the solitary tract (NTS) is the major site for termination of visceral sensory afferents contributing to homeostatic regulation of, for example, arterial pressure, gastric motility, and breathing. Whereas much is known about how different neuronal populations influence these functions, information about the role of glia remains scant. In this article, we propose that glia may contribute to NTS functions by modulating excitatory neurotransmission. We found that acidification (pH 7.0) depolarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 70 publications
3
45
0
Order By: Relevance
“…The inhibition of discharge capability, underlying Cnidaria survival, is in line with previous reports describing that prey/predator relationships may be compromised by marine water pollution [23]. In fact, the role of glutamate in synaptic transmission in the nucleus of the solitary tract (NTS) is dependent on pH [35]. It has also been demonstrated that acidity causes the nematocyst wall to collapse, which may contribute to decreased discharge capacity [41].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The inhibition of discharge capability, underlying Cnidaria survival, is in line with previous reports describing that prey/predator relationships may be compromised by marine water pollution [23]. In fact, the role of glutamate in synaptic transmission in the nucleus of the solitary tract (NTS) is dependent on pH [35]. It has also been demonstrated that acidity causes the nematocyst wall to collapse, which may contribute to decreased discharge capacity [41].…”
Section: Discussionsupporting
confidence: 82%
“…Acid-base balance in cells is directly related to the intracellular concentration of free H + , which is finely regulated to avoid cellular damage. Therefore, pH is a relevant homeostatic parameter, and the relationship between pH maintenance and cell function is well established in mammals, especially in neuronal cells [33,34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Activation of glial sodium/bicarbonate cotransporters leading to depolarization has also been proposed as one putative mechanism underlying their CO 2 chemosensitivity (39). In addition, studies in the nucleus of the solitary tract have proposed that extracellular acidification regulates synaptic transmission by compromising glial glutamate uptake (29).…”
Section: Discussionmentioning
confidence: 99%
“…The linear I-V relationship, indicating passive membrane conductance as first noted by Kuffler and Nicholls (1966), has emerged as a common property of astrocytes across species (humans: Schroder et al, 2000;Han et al, 2013;rat: Steinhauser et al, 1994;Kressin et al, 1995;Bergles and Jahr, 1997;Clark and Barbour, 1997;Kimelberg, 2000, 2001;Zhang et al, 2009;Uwechue et al, 2012;Huda et al, 2013; mouse: Matthias et al, 2003;Lalo et al, 2006;caiman: Zayas-Santiago et al, 2014). Much like the astrocyte membranes in each of these species, the fly astrocyte has a resting membrane potential that is similar to or more negative than the potassium equilibrium potential, low membrane resistance, and high membrane capacitance.…”
Section: Drosophila Astrocyte Intrinsic Properties Are Similar To Thomentioning
confidence: 99%